2017
DOI: 10.1049/iet-nbt.2016.0191
|View full text |Cite
|
Sign up to set email alerts
|

BBN conjugated GNPs: a new targeting contrast agent for imaging of breast cancer in radiology

Abstract: Using of targeted contrast agents in X-ray imaging of breast cancer can improve the accuracy of diagnosis, staging, and treatment planning by providing early detection and superior definition of tumour volume. This study demonstrates a new class of X-ray contrast agents based on gold nanoparticles (GNPs) and bombesin (BBN) for imaging of breast cancer in radiology. GNPs were synthesised in spherical shape in the size range of 15 ± 2 nm and conjugated with BBN followed by coating with polyethyleneglycol (PEG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The nanocomplex, conjugated with specific antibodies to target human epidermal growth factor receptor 2 (HER2) overexpressed in BC, provided significant information regarding the distribution of nanomaterial, and represents a new approach for cancer therapy and non-invasive treatment for soft-tissue tumors. 56 Moreover, we found that computed tomography (CT) 70,113,139,[144][145][146][147][148][149][150][151][152] is at the fifth position in terms of number of works related to BC, while other techniques are less used, including superconducting quantum interference device (SQUID), 94,153 surface enhanced Raman scattering (SERS), 81,[154][155][156][157][158][159] synchrotron X-ray micro-imaging (X-ray), 150,152,160,161 positron emission tomography (PET), 106,115,142,162 and fluorescence molecular tomography (FMT). 70,73 We reported that single-photon emission computed tomography (SPECT), 163 ultrasound imaging (US), 71 intermolecular quantum coherence (iMQC), 164 optical coherence tomography (OCT), 165 ultrashort echo time (UTE) 166 are in the last positions as imaging techniques used ( Fig.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanocomplex, conjugated with specific antibodies to target human epidermal growth factor receptor 2 (HER2) overexpressed in BC, provided significant information regarding the distribution of nanomaterial, and represents a new approach for cancer therapy and non-invasive treatment for soft-tissue tumors. 56 Moreover, we found that computed tomography (CT) 70,113,139,[144][145][146][147][148][149][150][151][152] is at the fifth position in terms of number of works related to BC, while other techniques are less used, including superconducting quantum interference device (SQUID), 94,153 surface enhanced Raman scattering (SERS), 81,[154][155][156][157][158][159] synchrotron X-ray micro-imaging (X-ray), 150,152,160,161 positron emission tomography (PET), 106,115,142,162 and fluorescence molecular tomography (FMT). 70,73 We reported that single-photon emission computed tomography (SPECT), 163 ultrasound imaging (US), 71 intermolecular quantum coherence (iMQC), 164 optical coherence tomography (OCT), 165 ultrashort echo time (UTE) 166 are in the last positions as imaging techniques used ( Fig.…”
Section: Imagingmentioning
confidence: 99%
“…In vitro (SKBR3, MDA-MB-231 cells) [159] Quantum Dots ─ FI Ex vivo (Tumor tisue) [172] Gold Nanoparticles HEPES, Bombesin, PEG X-ray In vitro / In vivo (T47D cells) [161] Superparamagnetic Iron Oxide Nanoparticles Fluorescein-5maleimide-labeled DARPin G3…”
Section: Mri Nirmentioning
confidence: 99%
“…Heidari and co-workers used the peptide based on a universal binding sequence (Lys-Gly-Gly-Cys-Asp-Phe-Gln-Trp-Ala-Val-bAla-His-Phe-Nle) to target breast cancer in vitro and in vivo with gold nanorods for photothermal therapy [39] as well as imaging [40] and they pointed out its several advantages in comparison to native bombesin sequence, such as overcoming the issues related with receptor heterogeneity in tumors and ameliorating renal clearance due to the negatively charged hydrophilic aspartic acid residue. Similarly, Salouti et al [41] and Jafari et al [42] proposed the application of this peptide in breast cancer imaging using gold and superparamagnetic iron oxide nanoparticles, respectively. Pan-bombesin was also shown to improve prostate cancer imaging [43,44].…”
Section: Accardo Et Al Analyzed the Performance Of Seven Different Gr...mentioning
confidence: 99%
“…Also, noncovalent bonding may be useful in this context (Figure 7). Successful attachment of the BBN analog to gold nanoparticles can be achieved by exploiting the interaction between nitrogen atoms in free amine groups and gold surface [19,41]. Ocampo-Garcia et al have developed a shelf-storage stable kit based on gold nanoparticles operating on this principle [18].…”
Section: Ligand Incorporationmentioning
confidence: 99%
“…Recent studies have shown that gold nanoparticles (AuNPs) are considered a clear choice in intratumroal drug delivery due to their ability to be functionalized with a variety of tumor-avid biomolecules, ideal hydrodynamic size for penetration across tumor cell membranes, and efficient matrix/receptors mediated active and passive internalization [9,15,16]. Recent studies on the efficacy of functionalized gold nanoparticles in treating various cancers provide illustrious examples about the realistic scope of gold-based nanomedicine in tumor therapy [17][18][19][20][21]. Certain phytochemicals such as Epigallocatechingallate (EGCG) from tea are electron rich.…”
Section: Introductionmentioning
confidence: 99%